MENINGKATKAN KETERAMPILAN MEMBUAT ANYAMAN KESET MELALUI ALAT BANTU PEMIDANG BAGI ANAK TUNAGRAHITA RINGAN KELAS VI/C DI SLB YAPEM TARUSAN - Yusrimelti - Yusrimelti (Universitas Negeri Padang, 2013)
The background of this research is the discovery of two students of class VI mild mental retardation / C who have difficulty in making a woven mat on while following subjects are given the skills of teachers, it is because the child can not mengayam neatly and tightly woven so that the child is not good and loose. In addition, in the implementation of classroom teachers mengayam skills have never used a tool pemidang not been given in the implementation of the learning process in schools mengayam skills. The purpose of this research is to improve the neatness woven mat through the use of assistive devices for children pemidang mild mental retardation class VI / C. This research is action research (classroom action research) that takes the form of collaboration. These actions were taken to two children sixth grade mild mental retardation / C in SLB YAPEM Tarusan. The results showed for the first cycle held five meetings in the learning process that starts from the setting tool, insert the tool into the fabric pemidang, mengayam patchwork, woven spruce, and assessment of the work of children. Based on the average value obtained by the students at the end of the first cycle can be seen that the AN before the given action I get a value of 30% of all the indicators are given. And after a given action I got 60%. While HG before given action I got 40% of all the indicators are given. After the action I was given to 50%. In the second cycle performed in five learning skills to make woven mat, where AN scored 80% on the implementation of the second cycle, and HG get a score of 70%. From the results presentation and analysis of the data it can be concluded that the use of the tools in the learning process skills pemidang make woven mats can be improved mild mental retardation in children of class VI / C in SLB YAPEM Tarusan. Thus it can be suggested to the schools, teachers, and researchers can use the following to pemidang aids in improving learning skills for other children.